Optimizing Graphene Oxide Film Quality: The Role of Solvent and Deposition Technique - Grazia Giuseppina Politano (C)
Graphene oxide (GO) is a promising material due to its high mechanical strength, electrical conductivity, and optical transparency, making it suitable for applications like optoelectronics and energy storage. This study focuses on a simplified method of depositing and characterizing GO films via drop casting, particularly using isopropanol and water as solvents, and compares the results with reference samples of graphene produced by chemical vapor deposition (CVD) and GO films deposited by electrophoretic deposition (EPD). The optical properties of these films were analyzed using Variable Angle Spectroscopic Ellipsometry (VASE). The study revealed that GO films prepared with isopropanol exhibited a lower refractive index compared to those using water. Therefore, the research highlighted the significance of solvent choice and deposition method on the overall film quality. This work provides insights into optimizing GO film properties through careful solvent selection, contributing to the broader understanding and application of GO in advanced technologies.